Neighborhood Environment and Poor Maternal Glycemic Control-Associated Complications of Gestational Diabetes Mellitus - Leela V. Thomas, PhD; Claudine T. Jurkovitz, MD, MPH; Zugui Zhang, PhD, FAHA; Mitchell R. Fawcett, MBA; M. James Lenhard, MD, FACP, FACE (Elsevier, 2024)
Introduction: Risk of complications due to gestational diabetes mellitus is increasing in the U.S., particularly among individuals from racial minorities. Research has focused largely on clinical interventions to prevent complications, rarely on individuals' residential environments. This retrospective cohort study aims to examine the association between individuals' neighborhoods and complications of gestational diabetes mellitus. Methods: Demographic and clinical data were extracted from electronic health records and linked to American Community Survey data from the U.S. Census Bureau for 2,047 individuals who had 2,164 deliveries in 2014-2018. Data were analyzed in 2021-2022 using Wilcoxon rank sum test and chi-square test for bivariate analyses and logistic regression for analysis of independent effects. All census tract-based variables used in the model were dichotomized at the median. Results: Bivariate analysis showed that the average percentage of adults earning <$35,000 was higher in neighborhoods where individuals with complications were living than in neighborhoods where individuals without complications were living (30.40%±12.05 vs 28.94%±11.71, p=0.0145). Individuals who lived in areas with ≥8.9% of residents aged >25 years with less than high school diploma had a higher likelihood of complications than those who lived in areas with <8.9% of such residents (33.43% vs 29.02%, p=0.0272). Individuals who lived in neighborhoods that had ≥1.8% of households receiving public assistance were more likely to have complications than those who lived in areas where <1.8% of households received public assistance (33.33% vs 28.97%, p=0.0287). Logistic regression revealed that the odds of deliveries with complications were 44% higher for individuals with obesity (OR=1.44; 95% CI=1.17, 1.77), 35% greater for individuals residing in neighborhoods with higher percentages of households living below the poverty level (OR=1.35; 95% CI=1.09, 1.66), and 28% lower for individuals from neighborhoods where a higher percentage of households had no vehicles available for transportation to work (OR=0.72; 95% CI=0.59, 0.89). Conclusions: Clinical interventions in concert with environmental changes could contribute to preventing maternal and neonatal complications of gestational diabetes mellitus.